Impact of Banhabaekchulcheonmatang (Banxia Baizhu Tianma Tang) and Hwangryeonhaedoktang (Huang Lian Jie Du Tang) on edoxaban: Herb-drug interaction study in healthy subjects - Cho, Seok-jin; Song, Jungbin; Kang, Dong Wook; Kim, Ju Hee; Kim, Hocheol; Chung, Hyewon; Cho, Hea-Young (Journal of ethnopharmacology, 2025)
Concurrent use of traditional herbal medicines and conventional drugs, particularly for stroke treatment, is widespread, raising concerns about potential drug interactions. This clinical study aimed to investigate interactions between edoxaban, a direct oral anticoagulant, and two traditional herbal medicines commonly used for stroke: Banhabaekchulcheonmatang (BBCT) and Hwangryeonhaedoktang (HRHDT). Korean healthy volunteers participated in a randomized, open-label, three-period, three-treatment, two-sequence clinical study. Treatments consisted of a single oral dose of edoxaban tablet (60 mg) in the presence or absence of multiple doses of BBCT or HRHDT three times daily for six days. Pharmacokinetic and pharmacodynamic parameters of edoxaban and its active metabolite M4 were assessed following administration of edoxaban alone or in co-administration with BBCT or HRHDT. When edoxaban was co-administered with BBCT or HRHDT, the area under the curve (AUC) of edoxaban remained unaffected. However, its peak concentrations (Cmax) were decreased by 18.5%–28.1%. Similarly, co-administration of edoxaban with BBCT or HRHDT slightly decreased the AUC of M4 and reduced its Cmax by 16.8%–27.1%. Results revealed that BBCT and HRHDT had a minor impact on pharmacokinetics of edoxaban and M4. Despite alterations in systemic exposures, all pharmacodynamic parameters of edoxaban derived from activated partial thromboplastin time and prothrombin time were equivalent irrespective of herbal medicine co-administration. These findings contribute to our understanding of potential interactions between conventional anticoagulants and traditional herbal medicines, highlighting the need for comprehensive evaluation in clinical practice. [Display omitted] •Clinical Herb-drug interactions between edoxaban and two traditional herbal medicines (BBCT and HRHDT) were investigated.•BBCT and HRHDT have a minor impact on edoxaban pharmacokinetics.•Co-administration of edoxaban with BBCT or HRHDT does not affect edoxaban's anticoagulant efficacy.•This study emphasizes the importance of a comprehensive evaluation of herb-drug interactions.